Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Berbantuan Film Animasi terhadap Keterampilan Menulis Narasi Siswa Kelas V Sekolah Dasar - Ramadhani, Wedi; Kurniaman, Otang; Sari, Intan Kartika (TSAQOFAH, 2023)
This study aims to ascertain how the Cooperative Learning Model Type Think Pair Share Assisted Animation Film influences the narrative writing skills of fifth grade elementary school students. In this study using the type of researchquasi experimental design. Data analysis techniques include descriptive data analysis techniques and inferential statistical analysis. Based on the resultspretest research found that the average students' narrative writing skills were experimental class 61,3 However, when they took the research posttest, after being treated with the Type Cooperative learning modelThink Pair Share Animated Film Assisted, flat Their average narrative writing skills increased by 82.5. Based on the results of the t test, a significance value of 0.000 is obtained, which means 0.000 <0.05, then ha is accepted and ho is rejected, meaning that the type of cooperative learning modelthink pair share assisted animation film has an effect on the narrative writing skills of class v students at SDN 188 Pekanbaru